STRATEGI OPTIMALISASI MANAJEMEN PELAYANAN PUBLIK DI TERMINAL MENGWI KABUPATEN BADUNG (Studi kasus: Peralihan Terminal Ubung ke Terminal Mengwi) - putu eka purnamaningsih; Kadek Wiwin Wismayanti (Universitas Mahendradatta Denpasar, 2021)
Mengwi Terminal is a type A type of terminal which began operations on October 23, 2017. The terminal has an area of 5 hectares now under the Land Transportation Management Center (BPTD) XII of Bali and West Nusa Tenggara Provinces. The research objective to be achieved is to obtain an actual picture of the constraints faced in the process of optimizing public service management in the Mengwi Terminal. This research uses descriptive qualitative method with data collection techniques in the form of interviews, observation, and documentation. The results of this study indicate that the optimization of public service management in the Mengwi Terminal is carried out, but not yet running optimally. Efforts made related to the optimization are already carried out socialization activities to the public and the autobus entrepreneurs (PO) as well as already provided 8 Trans Sarbagita bus units and the process of repairing facilities and infrastructure at the Mengwi Terminal.